Effects of the use of competitive intelligence in industrial SMEs - Emilio Placer-Maruri; Daniel Pérez-González; Pedro Soto-Acosta (Intangible Capital, 2016)
Purpose: The literature about Competitive Intelligence (CI), as an advanced process of information management orientated towards supporting strategic decision making, has focused on topics related to the definition of the concept and on analyzing its application and the results obtained by large firms and governments through case studies. The literature recognizes that fact that the evolution of this topic creates a need to delve deeper in its study while applying it to other types of organizations and studying the effects that Competitive Intelligence produces in greater depth. Therefore, this study's objective is to analyze the effects that the use of CI has on different financial and not financial variables within a sample of SMEs. Design/methodology: The work follows the classical research scheme with literature review, statement of hypotheses and application of quantitative empirical methodology, collecting information through questionnaires sent by email, for further processing and statistical testing using ANOVA models, which allow get results and conclusions. Findings: This study's contribution comes from providing a new way to focus on the effects of de CI in companies and goes further than most of the studies cases and big companies. Therefore, its contributions are to analyze the effect of the CI within a group of SMEs and, using an empiric methodology, to look for causal relationships through financial and non-financial variables and tests on the hypotheses. The results show that Competitive Intelligence improves SMEs' adaptation capacity to their environment, improves their innovation capacity and supports value creation in their businesses. Research limitations/implications: The lack in the literature from previous studies that focused on samples of SMEs makes it possible to provide guidance and to make comparisons with the work that we carried out here. The sample size (79 companies) makes it difficult to extrapolate results. In addition, in the future it would be more appropriate to identify and analyze variables of different business sectors. Originality/value: This work provides a step forward in measuring the effects generated by Competitive Intelligence in SMEs, making it possible to demonstrate that only case studies have been analyzed. It also incorporates an approach using financial and non-financial variables that can guide future research as well as companies that want to generate their own self-assessment systems.